2022
DOI: 10.3389/fmicb.2022.1051013
|View full text |Cite
|
Sign up to set email alerts
|

Construction of nucleus-directed fluorescent reporter systems and its application to verification of heterokaryon formation in Morchella importuna

Abstract: IntroductionMorchella importuna (M. importuna) is a rare fungus with high nutrition value and distinct flavor. Despite the successful artificial cultivation, its genetic characteristics and biological processes such as life cycle, reproductive system, and trophic mode remain poorly understood.MethodsConsidering this, we constructed pEH2B and pMH2B vectors by fusing M. importuna endogenous histone protein H2B with fluorescent proteins eGFP or mCherry, respectively. Based on the constructed pEH2B and pMH2B vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Lv et al (2018) first reported the construction of a genetic transformation system for M. importuna through an Agrobacterium -mediated method [ 41 ], and then the research team added nuclear localization tags to eGFP and mCherry fluorescence, respectively, with the help of this system, thus realizing the transformation of two different mating strains of M. importuna . The pairing of transformants showed that they can be well fused, which intuitively displayed the heterothallism of M. importuna [ 42 ]. The successful construction of a genetic transformation system would provide additional technical support for further study on gene function, regulation, and development in Morchella .…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lv et al (2018) first reported the construction of a genetic transformation system for M. importuna through an Agrobacterium -mediated method [ 41 ], and then the research team added nuclear localization tags to eGFP and mCherry fluorescence, respectively, with the help of this system, thus realizing the transformation of two different mating strains of M. importuna . The pairing of transformants showed that they can be well fused, which intuitively displayed the heterothallism of M. importuna [ 42 ]. The successful construction of a genetic transformation system would provide additional technical support for further study on gene function, regulation, and development in Morchella .…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
“…Studies related to “multiomics” and molecular biology technologies have also been encouraged. As a consequence, physiological, genetic, and biotechnological approaches have quickly become a new research hotspot and transformed morels into model species of macro-ascomycete cultivation [ 38 , 41 , 42 ]. Previously, there have been some reviews emphasizing the cultivation mode, nutrients and metabolism, active compounds, and life cycle [ 7 , 26 , 38 , 43 , 44 ], but less attention has been paid to aspects of paramount relevance, which have strongly affected a steady morel cultivation industry, including details of the basic principles of the cultivation technologies, the spawn technology, and characteristics related to the challenging cultivation stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, indoor cultivation in the United States has stagnated after a period of operation, and field cultivation in China has recently also suffered 70% non-profit situations in some areas [ 9 , 10 , 11 , 12 ]. As a consequence, there has recently been a comprehensive promotion of field cultivation based on deep knowledge development of basic biological foundations, such as the identification and characteristics of cultivable varieties [ 12 , 13 , 14 , 15 ], the identification of mating type genes [ 9 , 10 ], the characteristics of heterokaryons [ 16 , 17 , 18 , 19 , 20 , 21 ], nutritional metabolism [ 22 , 23 ] and “omics” technology [ 19 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, key questions related to the life cycle of Morchella remain far from completely understood [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%